Expression and Purification of Protein Complexes Suitable for Structural Studies Using Mammalian HEK 293F Cells. (13th February 2018) - Nigi, Irene; Fairall, Louise; Schwabe, John W.R.
Abstract: Prokaryotic expression systems have been widely used to express proteins for structural studies. Such expression systems have the advantage of being economical, straightforward and fast. However, for many eukaryotic proteins and particularly protein complexes, bacterial expression systems do not produce significant yields of soluble protein. This may result from failure to efficiently transcribe/translate the required protein or may result from the formation of insoluble aggregates known as inclusion bodies. Mammalian expression systems can often produce natively folded proteins, sometimes with native post‐translational modifications. However, such expression systems are underutilized due to the perception that they are costly, technically challenging and result in limited protein yields. In fact, HEK 293F cells are straightforward to grow, transfect with high efficiency and often produce significant yields of recombinant proteins. In this unit, we describe a method to express and purify milligram quantities of a human protein complex from HEK 293F cells grown in suspension transiently transfected with the appropriate plasmids. © 2017 by John Wiley & Sons, Inc.